Analisis Pengaruh Pertumbuhan Ekonomi dan Kesempatan Kerja Terhadap Pengangguran di Kabupaten Aceh Barat - Syahril Syahril (Syiah Kuala University, 2014)
The objective of the study is to examine whether economic growth and the rate of employment affect unemployment rate in Aceh Barat. Data used in the study were secondary data published by BPS and other relevant agencies. The results of the study revealed that economic growth has statistically negative relation with the rate of unemployment. The sign of employment variable was not consistent with relevant teory as it must have positive relation with unemployment rate. Nonetheless, F-test confirmed that economic growth and employment rate had statistically significant impact in explaning the rate of unemployment. As indicated with the coefficient of determination, 98.8% of variation in unemployment rate could be pointed out by the two independent variables.